Doing it our way? Recruitment and training strategies of foreign companies in Germany - Pilz, Matthias [Verfasser]; Finken, Lena [Verfasser] (My University, 2025)
“The “dual” model of vocational training is well established in many German companies, enabling them to train young talent to meet their existing and future demand for skilled labour. However, Germany’s system is unusual: most other countries organise training in an entirely different way. Over the past few decades, the accelerating pace of globalisation has prompted many foreign companies to set up in Germany, but the academic literature does not consider this group specifically, so it is unclear how subsidiaries of foreign companies meet their requirements for skilled labour. Training cultures are very different in their respective home countries, making this an interesting and beneficial issue to investigate. This study therefore explores how foreign companies with different training cultures manage recruitment and training when they set up in Germany with its dominant dual vocational training system.“ (author’s abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 5.3 Personalentwicklung; 370; Unternehmen; Ausländischer Arbeitgeber; Ausbildungsverhalten; Personalgewinnung